In Vitro Termiticidal Activity of Medicinal Plant Essential Oils Against Microcerotermes crassus - Chaiamon Chantarapitak; Jarongsak Pumnuan; Chaiwat Chanpitak; Somsak Kramchote (Insects, 2025)
values below 10 h at 250 µL/L and over 80% repellency at 100-500 µL/L within 3-12 h. Eugenol, the major constituent, showed comparable activity. In contrast, star anise oil, dominated by anethole, displayed weaker repellency but measurable termiticidal effects with a slower onset. These findings indicate that eugenol-rich oils may provide rapid-contact activity. In contrast, anethole-rich oils may offer slower but measurable termiticidal effects, suggesting distinct potential roles in future formulation development. The findings provide a foundation for developing nanoemulsion-based botanical termiticides with improved stability and field performance.
Keywords: Insect Pest Control Strategies; Insect and Arachnid Ecology and Behavior; Entomopathogenic Microorganisms in Pest Control